ANALISIS USAHA PEMBUATAN PUPUK ORGANIK CAIR DI DESA SRIWANGI KABUPATEN OKU TIMUR - Wardi Saleh (Jurnal Bakti Agribisnis, 2016)
The purpose of this research were to : (1) Determine the revenue in the business of making a liquid organic fertilizer in the village of East OKU District Sriwangi, (2) Determine the feasibility of liquid organic fertilizer financially from cow urine in the village of East OKU District Sriwangi. This research was conducted in September 2014 through to the finish, with a purposive sampling method, and also take samples of cow urine-making business in the village of East OKU District Sriwangi The study found that the average fiscal revenue POC production of 358 bottles of USD 3.58 million / production process POC-making business Sriwangi In the village, the average income of the business of making POC is Rp 1,460,399 / production processes and the average value of production BEP is 32 bottles.